The report on the Indian coronary intervention data for the year 2011 – National Interventional Council - Sivasubramanian Ramakrishnan; Sundeep Mishra; Rabin Chakraborty; K. Sarat Chandra; H.M. Mardikar (Indian Heart Journal, 2013)
The National interventional council of Cardiological Society of India has conventionally been presenting the data on various forms of cardiac interventions performed in the previous year at its annual meeting. Here we are reporting the data on coronary interventions done in India during the year 2011.